The right of communication to the public in the cloud: an EU perspective - Derclaye, Estelle (2012)
This paper examines the law relating to the right of communication to the public with reference to cloud storage and retrieval. It does so under the WIPO Internet treaties and EU statutory and case law, with some references to Member State statutory and case law when relevant. It focuses therefore on the liability of the cloud computing provider and the user for communication to the public, which, according to the law, includes making protected content available to the public. I leave aside the private international law issues as they are addressed by other speakers.